TEXT BOOK AND GENDER SOCIALIZATION AT ELEMENTARY SCHOOL: STUDY OF AN INDONESIAN TEXTBOOK PUBLISHED BY YUDISTIRA FOR LEVEL II AND V - Jatiningsih, Oksiana; Soesatyo, Yoyok (International Business Education Journal, 2008)
One of the education functions is socialization. It has role to continue or deconstruct certain value. In the context, besides teachers, textbooks have an important role to socialize values in connected with hidden curriculum in their materials. Gender values in hidden curriculum will socialize certain gender values to children. Together with gender value changes in a society, textbooks can either accelerate or impede deconstruction efforts of gender value from traditional to egalitarian ones.